Pengembangan Pembangkit Biogas dalam Kajian Sains Islam untuk Keberlanjutan Pelestarian Lingkungan - Sudibyo, Henny; Wresta, Arini (Kaunia: Integration and Interconnection Islam and Science Journal, 2025)
Biogas is a renewable energy derived from the degradation of organic materials, such as agricultural waste, livestock waste, and others. Several Qur'anic verses in Islam explicitly support the wise and effective utilization of natural resources; this includes the concept of sustainability and sustainable management of resources. “Eat [therefrom] and pasture your livestock. Indeed, in that are signs for those of intelligence.” is an example of biogas management' relationship with the Qur'an (QS. Thaha: 54). Biogas made from livestock manure is an example of wise resource utilization and is in line with Islamic teachings about not wasting natural potential. Using biogas as a renewable energy source reflects the concept of sustainability (istidamiyyah), which is highly encouraged in Islam. The use of biogas reduces the use of fossil fuels, reuses organic waste that normally pollutes the environment, and reduces greenhouse gas emissions. Biogas generation is closely related to Islamic teachings on environmental conservation, effective resource management, and the role of humans as khalifah on earth. By utilizing renewable energy such as biogas, Muslims can apply the teachings of the Qur'an to protect the Earth, prevent damage, and maintain the balance of the ecosystem.